Preventing Infection by Human Cytomegalovirus - Plotkin, Stanley A (J Infect Dis, 2020)
The way to a successful vaccine against human cytomegalovirus is hampered by the peculiar biology of this infection. However, some candidate vaccines have been shown to protect seronegative women and transplant recipients, and we should know soon whether they can prevent congenital infection.